Molecular Mechanisms for cAMP-Mediated Immunoregulation in T cells – Role of Anchored Protein Kinase A Signaling Units - Wehbi, Vanessa L.; Taskén, Kjetil (Frontiers in Immunology, 2016)
The cyclic AMP/protein kinase A (cAMP/PKA) pathway is one of the most common and versatile signal pathways in eukaryotic cells. A-kinase anchoring proteins (AKAPs) target PKA to specific substrates and distinct subcellular compartments providing spatial and temporal specificity for mediation of biological effects channeled through the cAMP/PKA pathway. In the immune system, cAMP is a potent negative regulator of T cell receptor-mediated activation of effector T cells (Teff) acting through a proximal PKA/Csk/Lck pathway anchored via a scaffold consisting of the AKAP Ezrin holding PKA, the linker protein EBP50, and the anchoring protein phosphoprotein associated with glycosphingolipid-enriched microdomains holding Csk. As PKA activates Csk and Csk inhibits Lck, this pathway in response to cAMP shuts down proximal T cell activation. This immunomodulating pathway in Teff mediates clinically important responses to regulatory T cell (Treg) suppression and inflammatory mediators, such as prostaglandins (PGs), adrenergic stimuli, adenosine, and a number of other ligands. A major inducer of T cell cAMP levels is PG E2 (PGE2) acting through EP2 and EP4 prostanoid receptors. PGE2 plays a crucial role in the normal physiological control of immune homeostasis as well as in inflammation and cancer immune evasion. Peripherally induced Tregs express cyclooxygenase-2, secrete PGE2, and elicit the immunosuppressive cAMP pathway in Teff as one tumor immune evasion mechanism. Moreover, a cAMP increase can also be induced by indirect mechanisms, such as intercellular transfer between T cells. Indeed, Treg, known to have elevated levels of intracellular cAMP, may mediate their suppressive function by transferring cAMP to Teff through gap junctions, which we speculate could also be regulated by PKA/AKAP complexes. In this review, we present an updated overview on the influence of cAMP-mediated immunoregulatory mechanisms acting through localized cAMP signaling and the therapeutical increasing prospects of AKAPs disruptors in T-cell immune function.